Global variation in antibiotic prescribing guidelines and the implications for decreasing AMR in the future - Jamil, Emmama; Saleem, Zikria; Godman, Brian; Ullah, Matti; Amir, Afreenish; Haseeb, Abdul; Meyer, Johanna C.; Qamar, Muhammad Usman; Almarzoky Abuhussain, Safa S. (Frontiers in Pharmacology, 2025)
IntroductionAntimicrobial resistance (AMR) has become a global burden, with inappropriate antibiotic prescribing being an important contributing factor. Antibiotic prescribing guidelines play an important role in improving the quality of antibiotic use, provided they are evidence-based and regularly updated. As a result, they help reduce AMR, which is a critical challenge in low- and middle-income countries (LMICs). Consequently, the objective of this study was to evaluate local, national, and international antibiotic prescribing guidelines currently available—especially among LMICs—and previous challenges, in light of the recent publication of the WHO AWaRe book, which provides future direction.MethodologyGoogle Scholar and PubMed searches were complemented by searching official country websites to identify antibiotic prescribing guidelines, especially those concerning empiric treatment of bacterial infections, for this narrative review. Data were collected on the country of origin, income level, guideline title, year of publication, development methodology, issuing organization, target population, scope, and coverage. In addition, documentation on implementation strategies, compliance, monitoring of outcome measures, and any associated patient education or counseling efforts were reviewed to assess guideline utilization.Results/findingsA total of 181 guidelines were included, with the majority originating from high-income countries (109, 60.2%), followed by lower-middle-income (40, 22.1%), low-income (18, 9.9%), and upper-middle-income (14, 7.7%) countries. The GRADE methodology was used in only 20.4% of the sourced guidelines, predominantly in high-income countries. Patient education was often underemphasized, particularly in LMICs. The findings highlighted significant disparities in the development, adaptation, and implementation of guidelines across different WHO regions, confirming the previously noted lack of standardization and comprehensiveness in LMICs.ConclusionSignificant disparities exist in the availability, structure, and methodological rigor of antibiotic prescribing guidelines across countries with different income levels. Advancing the development and implementation of standardized, context-specific guidelines aligned with the WHO AWaRe framework—and supported by equity-focused reforms—can significantly strengthen antimicrobial stewardship and help address the public health challenge of AMR.